America! America! - Buggey, JoAnne (Glenview, Ill. : Scott, Foresman, 1977)
A textbook presenting a general overview of United States history from early Indian civilizations to the present day.
Includes bibliographies and index.
Keywords: United States -- History -- Juvenile literature; United States -- History